Managing and Overcoming Barriers to Inclusive Education: A Case Study - Pratiwi, Hardiyanti (Indonesian Research Journal in Education |IRJE|, 2024)
Private early childhood education encounters significant challenges in delivering inclusive education. This study investigates management strategies in these institutions, focusing on RA Ulumul Qur'an Al-Madani in South Kalimantan, a pilot for inclusive education. Using a case study approach, data was gathered through interviews, observation, and document analysis. The findings indicate a structured approach to management across various aspects. Admission procedures involve engaging parents, assessing children's special needs, and forming suitable groups. Curriculum management includes modifications, substitutions, and providing individualized education programs. Strategies to enhance teacher competency include selection, training, and expert support. Facility management focuses on planning, maintenance, and procurement of necessary resources with external support. Public relations utilize social media for community engagement and Whatsapp group for effective communication. Effective management positively impacts student learning, parent involvement, and children's rights. The study underscores collaboration among government, experts, and communities to bolster inclusive education quality, particularly in private ECE institutions.